A case series of mucormycosis and aspergillus coinfection in post-covid-19 patient with uncontrolled diabetic - Anita, Anita; Kumar, Shailesh; Kumari, Namrata; Rajpal, Kamlesh; Kumar, Santosh; Singh, Rakesh Kumar (Indian Journal of Case Reports, 2021)
Mucormycosis is an angioinvasive infection caused by fungi Mucorales which mainly occurs in immunocompromised patients. Aspergillosis is also an opportunistic fungal infection caused by Aspergillus species. Coinfection with mucormycosis and aspergillosis is very rare and very few cases were published in the literature till now. There is an increase in the incidence of mucormycosis infection in post-COVID-19 patients. Here, we are going to report a case series of three cases of combined infection of mucormycosis with Aspergillus. All three patients were treated with extensive surgical debridement and intravenous liposomal amphotericin B. Even after aggressive treatment, the mortality rate is high in these types of patients.